The Effect of Factors on Satisfaction and Reuse Intention of OVO E-Wallet - Farizka Hayyu Artanti; Sumayyah Aziz; Dr. Osly Usman, M.Bus Syst (Journal of Strategic Marketing and Innovation, 2025)
This research study examines the factors such as ease of use, brand trust, and security of transaction that influence customer satisfaction and their intention to continue using the OVO e-wallet. The factors analyzed include ease of use, transaction security, and brand trust. The study focuses on OVO users in the Jakarta, Bogor, Depok, Tangerang, and Bekasi areas, with a sample size of 100. The data in this study is collected through an online survey and analyzed using SmartPLS 4. The results indicate that ease of use and transaction security positively impact great customer experience and their intention to continue using the OVO e-wallet. However, brand trust does not significantly affect customer satisfaction. These findings highlight the importance of ease of use and transaction security in enhancing customer satisfaction and the continuance intention for using the OVO e-wallet.